(untitled) (Physical Education, Health and Social Sciences, 2026)
Introduction: Tibial plateau fractures contribute 1% of all fractures and are classically sustained with high-energy mechanisms. Injuries to the vasculature, nerves, ligaments, menisci, and surrounding compartments have all been linked to tibial plateau fractures 1. The outcome of this study will be helpful in designing effective therapeutic protocols for patients care. Objective: To determine the functional outcome of open reduction and internal fixation for surgical treatment of tibial plateau fracture. Study Design: Descriptive Study Study Setting: Department of Orthopedic surgery, Khyber Teaching Hospital, Peshawar. Study Duration: 23-07-2023—23-07-2024 Subject and Methods: We conducted this study on 86 patients of both genders having age between 18 to 70 years presenting with tibial plateau fracture diagnosed on plain radiograph. Patient with ipsilateral femur, foot fractures and concomitant lower extremity fractures were excluded. Functional outcome of open reduction and internal fixation was determined. Results: This study was conducted on 86 patients. The mean age of the patients was 46.98±15.82 years. According to the functional outcome we observed that 60 (69.8%) patients had excellent outcome, good outcome was seen in 15 (17.4%) patients, fair outcome was seen in 7 (8.1%) patients and poor outcome was seen in 4 (4.7%) patients. Conclusion: From our study we conclude that the functional outcome of open reduction and internal fixation for surgical treatment of tibial plateau fracture was excellent in 60 (69.8%) patients, good 15 (17.4%), fair 7 (8.1%) and poor in 4 (4.7%) patients.